Extension of X-parameters to include long-term dynamic memory effects - Verspecht, J.; Horn, J.; Betts, L.; Gunyan, D.; Pollard, R.; Gillease, C.; Root, D.E. (2009 IEEE MTT-S International Microwave Symposium Digest, 2009)
A new unified theory and methodology is presented to characterize and model long-term memory effects of microwave components by extending the poly-harmonic distortion (PHD) model to include dynamics that are identified from pulsed envelope X-parameter measurements on an NVNA. The model correctly predicts the transient RF response to time-varying RF excitations including the asymmetry between off-to-on and on-to-off switched behavior as well as responses to conventional wide-bandwidth communication signals that excite long-term memory effects in power amplifiers. The model is implemented in the ADS circuit envelope simulator.